(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2014)
Introduction: A retrospective study to explore the epidemiology and clinical characteristics of Tuberculosis among Saudis, migrant workers from SAARC and other nations. The objective of this study is to study the prevalence and clinical features of Tuberculosis among Saudis & other migrant workers in central Saudi Arabia. Methodology: A Retrospective study was conducted based on the secondary data pertaining to the patients registered at Regional TB center in Buraidah Central Hospital from Jan 2005 to December 2009. Results: A total of 355 case records were included of which 187 cases are from Saudi Arabia and remaining 168 were from South Asian countries. Cough with expectoration, fever with evening rise, loss of appetite were the chief clinical presentations. Out of the total non Saudi patients, the Indonesian patients contribute to 74 (21%) followed by Indians 39 (11%), Nepalese 12 (3.4%), Philippines & Bangladesh with 9 cases each (2.5%), and Pakistan with 8 cases (2.3%). Among the total cases, there were 341 (96%) new cases, 12 (3.4%) relapse cases and 2 (0.6%) defaulters. Conclusion: Prevalence of TB among migrant is relatively high. Preventive measures for early diagnosis should be performed especially among migrant workers from countries with high-prevalence of Tuberculosis. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(2); 21-26 DOI: http://dx.doi.org/10.3126/saarctb.v10i2.9709